The Internal Conflict of Syria in The Construction of Al-Jazeera - Windy Dermawan; Nugrah Nurrohman; Akim (International Journal of Islamic Thought and Humanities, 2024)
This study aims to analyze Al-Jazeera's contribution on the dynamics of the internal conflict in Syria. The method used in this study is qualitative descriptive method with Nicholas Onuf's constructivism approach. Researchers collected primary data by interviewing a number of relevant informants and secondary data through documentation studies, archival, document-based research, and internet-based research. This study found that the media not only functions as a monitor, but can also be used as a driving force by state actors. In addition, it was found that there were actions taken by al - Jazeera as an agent and information service provider which encourages the Syrian people to move and ultimately stimulates the internal conflict between the Syrian regime and the Syrian people. This study has limitation in concern to the dynamics of the conflict in the Middle East extensively, which also participate to provide settings to the internal conflict in Syria. However, this study is able to contribute to the development of the repertoire of International Relations Studies, especially in the understanding of the contribution of global media to the socio-political dynamics of a country.